Are there long-run diversification gains from the Dow Jones Islamic finance index? - Balcilar, Mehmet; Jooste, Charl; Hammoudeh, Shawkat; Gupta, Rangan; Babalos, Vassilios (Routledge Journals, Taylor & Francis Ltd, 2015)
We compare a nonlinear (time-varying) cointegration test with the standard cointegration test in studying the long-run relationship of the Dow Jones Islamic finance index with three other conventional global equity market indices. Our results show that there is a long-run nonlinear cointegrating relationship between the Dow Jones Islamic stock market index and other conventional stock market indices, which is not picked up by the linear cointegration test. Thus, Islamic markets seem to offer little, if any, long-run diversification to international investors.
Keywords: C5; C12; G1; Islamic and conventional finance; time-varying cointegration